Peripheral N- and C-terminal domains determine deactivation kinetics of HCN channels. - Ishii, T.M.; Nakashima, N.; Takatsuka, K.; Ohmori, H. (Biochemical and Biophysical Research Communications, 2007)
Among four subtypes of mammalian HCN channels, HCN1 has the fastest activation and deactivation kinetics while HCN4 shows the slowest. We previously showed that the activation kinetics are determined mainly by S1, S1-S2, and the S6-cyclic nucleotide binding domain. However, the effects of those regions on the deactivation kinetics were relatively small. Therefore, we investigated the structural basis for deactivation kinetics. Substitution of the core region (from S3 to S6) between HCN1 and HCN4 did not affect deactivation kinetics. This suggests that the peripheral regions (outside of S3 to S6) determine subtype-specific deactivation kinetics. Furthermore, we examined whether peripheral regions determined the deactivation kinetics across species by introducing the core region of DMIH (Drosophila homologue) into both HCN1 and HCN4. The DMIH core with HCN1 activated and deactivated more than threefold faster than that with HCN4. Taken together, the peripheral domains are diversified to create distinct kinetics.